2013
DOI: 10.1590/s1806-37132013000500005
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis transmembrane conductance regulator mutations at a referral center for cystic fibrosis

Abstract: OBJECTIVE: To determine the frequency of six mutations (F508del, G542X, G551D, R553X, R1162X, and N1303K) in patients with cystic fibrosis (CF) diagnosed, at a referral center, on the basis of abnormal results in two determinations of sweat sodium and chloride concentrations. METHODS: This was a cross-sectional study involving 70 patients with CF. The mean age of the patients was 12.38 ± 9.00 years, 51.43% were female, and 94.29% were White. Mutation screening was performed with polymerase chain reaction (for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Mutation G542X (class I), characterized by a change that results in the absence of the CFTR protein, was the second most prevalent in this sample of patients (six alleles, 7.14%), and its frequency is estimated between 2.7 and 8.5% in Brazil. 11 , 12 This mutation is responsible for the high incidence of meconium ileus. 13 In our sample, most patients who presented with one allele of the mutation G542X also had pancreatic insufficiency (66.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Mutation G542X (class I), characterized by a change that results in the absence of the CFTR protein, was the second most prevalent in this sample of patients (six alleles, 7.14%), and its frequency is estimated between 2.7 and 8.5% in Brazil. 11 , 12 This mutation is responsible for the high incidence of meconium ileus. 13 In our sample, most patients who presented with one allele of the mutation G542X also had pancreatic insufficiency (66.7%).…”
Section: Discussionmentioning
confidence: 99%
“…The research suggested a greater influence of other factors, such as gene modulation and poor treatment adherence, on the higher early mortality. 10 Most study participants were homozygous (n=15; 30%) or heterozygous (n=15; 30%) for the DeltaF508 mutation, totaling 45 (45%) of one hundred alleles; this is the most prevalent and studied CFTR gene mutation in the world. [2][3][4]7,10 It belongs to class II, meaning lack of functional CFTR protein and association with more severe CF phenotypes, with early respiratory symptoms, reduced pulmonary function, and pancreatic insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the participants were categorized into four groups according to the most prevalent mutation, DeltaF508: DeltaF508/DeltaF508, DeltaF508/other mutation, other mutation/other mutation, and other mutation/absence of mutation. We chose this grouping, already used in previous studies, 10,11 due to the high variability of these mutations in a small sample, in addition to limitations regarding the functional classification of CFTR gene mutations. 7 Participants with only one mutation identified were not excluded from the study if the diagnosis was confirmed by the two sweat tests, with chloride values equal to or greater than 60mEq/L, and by the presence of at least one phenotypic characteristic of CF.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was obtained by direct extraction from peripheral blood lymphocytes according to standard procedures [ 31 ]. CFTR mutations were determined in the following order: F508del identification using the primers forward 5′-GGC ACC ATT AAA GAA AAT ATC-3′ and reverse 5′-TGG CAT GCT TTG ATG ACG C-3′ [ 25 , 26 ]; CFTR exon sequencing, including exon/intron boundaries, performed as previously described [ 24 , 32 , 33 ]; duplication, deletion, and LOH identification using the SALSA MLPA Kit P091-C1 CFTR-MRC-Holland (MRC-Holland, Willem Schoutenstraat, DL Amsterdam, Netherlands) performed according to the manufacturer instructions; and 1584–18672 pb A>G (intron 10) identification performed as previously described [ 34 ].…”
Section: Methodsmentioning
confidence: 99%